If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5r = 7 + -4r + 8 Reorder the terms: -5r = 7 + 8 + -4r Combine like terms: 7 + 8 = 15 -5r = 15 + -4r Solving -5r = 15 + -4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '4r' to each side of the equation. -5r + 4r = 15 + -4r + 4r Combine like terms: -5r + 4r = -1r -1r = 15 + -4r + 4r Combine like terms: -4r + 4r = 0 -1r = 15 + 0 -1r = 15 Divide each side by '-1'. r = -15 Simplifying r = -15
| (-3a)10=2a | | (-20)=(k)-7 | | -29+-33= | | -3a*10=2a | | 4w+10=80 | | 7+7x=19+x | | 5(4+7x)= | | g(x)=-4x+1 | | 12(0)-15y=18 | | -3x-2x=-3+4 | | x*-13=-40 | | 5E=120 | | -3-2x=-3+4 | | 3x+4=-2+x | | -2y+2=6 | | 24=3(x+3)-8x | | 4-5=11 | | 4+2(2u-4)=-2(9u-3)+4u | | 5g+5x=115-25 | | 12x-15(0)=18 | | h(x)=5x+3 | | -5n+8=-2 | | y=sin(2t) | | 3x+4x-4=31 | | -x=(5x+3)(3k+1) | | x^2-0.44x+c=0 | | -2y-7=-3 | | 4(3+d)=9-5(3+d) | | 6x-4-3x+1=12 | | 5x+(-2x)=9+7 | | 4-5=h | | f(x)=x^2-16x+28 |